Pengaruh Pemberian Sari Buah Stroberi Terhadap Kerusakan Histologis Sel Ginjal Mencit Akibat Paparan Parasetamol - Pratita Komalasari; . Muthmainah; Bhisma Murti (Nexus Kedokteran Translasional, 2013)
Background: Strawberry essence is known to contain vitamin C, anthocyanins and elagic acid. It has potent antioxidant properties and anti-inflammatory. This study aims to examine the effects of strawberry essence in preventing histologic damage renal cell of mice (Mus musculus). Methods: The study used Randomized Controlled Trial (RCT) design. The samples of 28 male mice (Mus musculus) Swiss Webster strain, aged 2-3 months, body weight 20 grams were divided into 4 groups: KK (aquadest), KP I (aquadest + paracetamol), KP II (Paracetamol+Strawberry essence dose 416 mg/20 g BB), KP III (Paracetamol+Strawberry essence dose 832 mg/20 g BB). The treatment was given for 14 days, except paracetamol was given only on day 12 th, 13 th, 14 th. On day 15th mice were sacrificed by neck dislocation. Then right and left renal of mice were taken. From each renal was made two histological preparations. Renal preparations were made ??by the method of paraffin blocks with Haematoxylin Eosin staining (HE). Observations of renal used a light microscope magnification of 1000 times. The number of damaged cells from each of 50 cells in the renal proximal tubule were counted. Data were analyzed by One-Way Analysis of Variant Test (ANOVA) and Post Hoc test (?=0,05). Results: Mean of KK = 7.61 1.786, KP I = 37.07 2.905, KP II = 29.64 3.540, KP III = 22.39 3.403. There were significant differences of the mean number of damage cells in all pairs of groups (KK-KP I, KK-KP II, KK-KP III, KP I-KP II, KP I KP III, and KP II-KP III). Conclusion: The Strawberry essence (Fragaria x annanassa) could prevent histological damage renal cells of mice exposed to paracetamol, but it could not give the same effect as the KK (p < 0.001). Keywords: Strawberry Essence, paracetamol, histologic damage renal cell